Фактори впливу на кредитоспроможність підприємств – позичальників банків - Соколова, Л. В.; Гаврилович, О. В. (ХНУРЕ, 2016)
This scientific work is devoted to studying the impact of environmental factors on the creditworthiness of enterprises. It is necessary to identify these factors and to consider their impact on the creditworthiness of enterprises.
Keywords: кредитоспроможність підприємств; підприємства-позичальники банків